Clinical and Aberrometric Evaluation of a New Monofocal IOL with Intermediate Vision Improvement - Alessandro Bova; Stefano Vita (Journal of Ophthalmology)
Purpose. The aim of the study was to evaluate the visual outcomes, aberrometric results, and subjective and objective optical qualities 12 months after implantation of a new monofocal intraocular lens (Physiol IsoPure 1.2.3) in comparison with a standard monofocal intraocular lens (Tecnis PCB00). Materials and Methods. Cataract patients without ocular comorbidities had bilateral implantation of the IsoPure IOL or the PCB00 IOL. One month after eye surgery, the visual acuity and monocular defocus curve were assessed. Twelve months after surgery, the visual acuity, binocular defocus curve, contrast sensitivity, and subjective/objective optical quality were assessed. Furthermore, wavefront analysis was performed. The primary endpoint was the best distance correct/uncorrected visual acuity at intermediate and far distances. The secondary endpoint was an aberration evaluation of the IOLs and contrast sensitivity. Results. The study comprised a total of 42 patients (84 eyes). Monocular and binocular uncorrected and corrected distance were similar between groups, and uncorrected intermediate visual acuity was significantly higher in the IsoPure group. There was no difference in contrast sensitivity and subjective and objective optical qualities. The optical aberrations at 3.0 and 5.0 mm aperture diameters were similar in both groups. Conclusion. The IsoPure IOL, based on greater depth of focus than the aspheric monofocal IOL, may offer a good option for the distance and intermediate vision without increasing optical aberrations and any photic phenomena.